Caracterización De La Planeación Tributaria Para La Mitigación De Sanciones Impuestas por La Dian A Las Pequeñas Empresas - Bello Naranjo, Erika Johana (Universidad Antonio Nariño, 2022)
Currently, in Colombia, tax burdens are increasing more and more through tax reforms, which makes it necessary for small businesses to opt for the need to adopt tax planning, in order to minimize the risk of sanctions imposed by the DIAN, and at the same time take advantage of tax benefits and incentives that good tax planning would give you. The present work is based on studying the importance of tax planning for small businesses, therefore, it began with one with an approach analyzing the variables of why small businesses do not choose to carry out tax planning, the risks they run and the benefits and strategies that the taxpayer would choose. Then some objectives are presented, which are intended to identify the shortcomings, risks and strategies for the taxpayer and subsequently provide a solution. Then a framework is presented which is based on general definitions, terminology to be treated, background in order to provide greater clarity of this proposal, then we present the methodology which was based on qualitative descriptive research, which allowed enriching the work. And finally we expose the results, giving solution to the objectives. To achieve the results, the variables and shortcomings of why small businesses do not opt for tax planning were analyzed, then we expose the risks incurred by the taxpayer and finally, through regulations, we analyze the strategies so that the taxpayer opts for tax planning. tax that allows you to take advantage of tax benefits.